Pengaruh Penggunaan E-Modul berbasis Flip HTML 5 dalam Pembelajaran Daring terhadap Motivasi Belajar Siswa Kelas V SD - M. Misbachul Huda (STKIP AL HIKMAH SURABAYA, 2022)
This research aims to determine the effect of the Flip Html 5-Based E-Module in online learning on the learning motivation of fifth grade elementary school students. Fifth grader students are one of the group of students of the negligent generation, which is a generation that is very close to technology. In online learning, the use of gadgets is a condition that is very suitable for the characteristics of this generation. The presence of e-modules that can be accessed from students' devices anywhere and anytime as a learning resource is one form of online learning innovation. This research is a quantitative research with an experimental form. The experimental design used is a posttest only control design. The research population is the fifth grader students of SDN Kepanjen 2 Jombang in the 2020/2021 academic year. The sample selection technique used random sampling, obtained by class VB and VC students as the research sample. The instrument used is an ARCS model of motivation questionnaire. The process of calculating the overall statistical data is carried out with the help of the IBM SPSS 26 application. The result is the Sig value. (2-tailed) P < 0.05 and the value of t count is greater than t table so that the research hypothesis Ho is rejected and Ha is accepted. These results indicate that the E-Module based on Flip HTML 5 in online learning has an effect on the learning motivation of fifth grade elementary school students. The influence of the use of e-modules in online learning on students' learning motivation in elementary schools has implications for the need for teachers to increase the variety of various aspects of learning. Variations in online learning are not only in learning resources, but also in media, displays, and learning strategies.